2017
DOI: 10.3892/etm.2017.5244
|View full text |Cite
|
Sign up to set email alerts
|

Acute kidney injury in cancer patients and impedance cardiography‑assisted renal replacement therapy: Experience from the onconephrology unit of a Chinese tertiary hospital

Abstract: Abstract. Acute kidney injury (AKI) in cancer patients may disrupt anticarcinogenic treatment and greatly increase associated mortality rates. The present study reported on the management of cancer patients with AKI and, from the nephrologic viewpoint, on the significance of fine volume control during the continuous renal replacement therapy (CRRT). The records of 117 cancer patients with AKI treated over three years were reviewed and their data were compared with those of 120 healthy controls. AKI was defined… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
4
0

Year Published

2019
2019
2020
2020

Publication Types

Select...
4

Relationship

3
1

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 32 publications
0
4
0
Order By: Relevance
“… 16 We found that a multidisciplinary therapeutic approach was vital in managing critically ill cancer patients with AKI. 17 More recently, the survival of patients with severe COVID-19 pneumonia reportedly depended on a similar approach. 18 To further highlight the MDT concept, we describe two cases of AKI in patients with GN and mTSS.…”
Section: Discussionmentioning
confidence: 99%
“… 16 We found that a multidisciplinary therapeutic approach was vital in managing critically ill cancer patients with AKI. 17 More recently, the survival of patients with severe COVID-19 pneumonia reportedly depended on a similar approach. 18 To further highlight the MDT concept, we describe two cases of AKI in patients with GN and mTSS.…”
Section: Discussionmentioning
confidence: 99%
“…A unique entity, namely, the Page kidney, was considered in this case with the associated hypertension after subcapsular hematoma, and the management required sufficient fluid control[ 12 ]. In this respect, our patients on maintenance hemodialysis generally manifested good Kt/V in both a cross-sectional study[ 13 ] and 10-year follow-up[ 14 ], and the critically ill patients receiving continuous renal replacement therapy had fine volume control[ 15 ]. Therefore, it is highly unlikely that the observed pleural effusion was derived from fluid overload.…”
Section: Discussionmentioning
confidence: 99%
“…Then, hematogenous dissemination of the infection to central nervous system in such patients is not uncommon and diagnostic delay often leads to a fatal outcome 46. Moreover, spurious laboratory results (such as unexplained hypernatremia) require extra vigilance as they may be the only precursory indicative of an insidious yet progressive disorder 47. Finally, an effective therapeutic decision clearly depends on multidisciplinary collaboration with the participation of specialists in microbiology and pharmacology 30.…”
Section: Discussionmentioning
confidence: 99%